Hypoperfusion in Supramarginal and Orbital Gyrus, Position Discrimination Test, and Microsaccades as a Predictor of Pisa Syndrome in Parkinson’s Disease - Asako Yoritaka; Tetsuo Hayashi; Keiko Fusegi; Sachiko Nakayama; Jun Haneda; Nobutaka Hattori (Parkinson's Disease)
Patients with Parkinson’s disease (PD) experience significantly reduced quality of life when PD is complicated with Pisa syndrome (PS). PS is a postural abnormality associated with a lateral bending of the trunk, causing the patient to lean to one side. Microsaccades during fixation are transmitted to the visual cortex, and this gaze movement may be impaired in PD. We aimed to detect presymptomatic signs of PS. We enrolled 50 patients with PD without dementia and investigated the visual systems in patients with concurrent PD and PS based on a Romberg ratio of<1.0. Gaze analysis, pupil diameter, stabilization tests, neuropsychological tests, and cerebral perfusion scintigraphy were reviewed and statistically analyzed. Two years later, we divided the patients into three groups as follows: PISA++ (patients who had PS at enrollment), PISA-+ (patients without PS that developed PS during the 2-year period), and PISA-- (patients without PS that did not develop PS during the 2-year period). The PISA-+ group exhibited a significantly higher daily levodopa dose and longer fixations, as well as lower position discrimination, Wechsler Adult Intelligence Scale-Third Edition blocking, and blood flow in the left supramarginal and orbital gyri than that in the PISA-- group. The PISA++ group showed a significantly longer fixation time and lower Mini-Mental State Examination score, Romberg ratio of area, amplitude, velocity of microsaccades, and blood flow in the left precuneus and cuneus than that in the PISA-+ group. Before the onset of PS, hypoperfusion occurred in the correlative visual cortex and the position discrimination test. Patients with PS have reduced saccades and slow microsaccades.